Keeping distance with a telepresence robot: A pilot study - Leoste, Janika; Heidmets, Mati; Virkus, Sirje; Talisainen, Aleksei; Rebane, Martin; Kasuk, Tiina; Tammemäe, Kalle; Kangur, Katrin; Kikkas, Kaido; Marmor, Kristel (Frontiers in Education, 2023)
Telepresence robots (TPRs) are the subject of an emerging field of application and research that has recently received attention from various disciplines. Most of the relevant research has been done in computer science so far, while the interest from psychology and education has been relatively modest. Proximity plays an important role in personal interactions. Although human spatial behaviour has been widely studied in social psychology, little attention has been paid to the spatial behaviour of humans and TPRs. The purpose of this paper is to present the results of a pilot study that investigated a certain aspect of spatial behaviour – physical proximity or interpersonal distance – based on Hall’s (1969) four social zones of interpersonal distance that characterise Western culture: intimate, personal, social, and public. The study conducted an experiment involving participants both in person and via TPRs, using the Double 3 TPRs in various simulated situations. According to the findings, most participants maintained a communication distance of 60 to 160 cm when interacting with a TPR. In line with Hall's theory, this is the borderline between personal and social distance, quite similar to normal human-to-human social communication. Status and previous relationship did not play any role in the choice of communication distance, but there were significant gender differences. On average, male participants chose a shorter distance to interact with TPRs compared to female participants. Persons with previous computer gaming experience chose a significantly shorter communication distance compared to persons with no such experience. A little more than half of the participants found the method of communication through TPRs to be pleasant.